2012
DOI: 10.1128/iai.05541-11
|View full text |Cite
|
Sign up to set email alerts
|

LipC (Rv0220) Is an Immunogenic Cell Surface Esterase of Mycobacterium tuberculosis

Abstract: We have reported previously the identification of novel proteins of Mycobacterium tuberculosis by the immunoscreening of an expression library of M. tuberculosis genomic DNA with sera obtained from M. tuberculosis-infected rabbits at 5 weeks postinfection. In this study, we report the further characterization of one of these antigens, LipC (Rv0220). LipC is annotated as a member of the Lip family based on the presence of the consensus motif "GXSXG" characteristic of esterases. Although predicted to be a cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Bioinformatically no signal sequence was identified in Rv1497 protein [3,25] while BlaC was shown to posses signal sequence [26]. Few Lip gene family members (LipC, LipF), have been predicted as cytoplasmic, while later on these were confirmed as extracellular or membrane bound [27,28]. Therefore, the localization of Rv1497 needed to be explored further in detail.…”
Section: Discussionmentioning
confidence: 95%
“…Bioinformatically no signal sequence was identified in Rv1497 protein [3,25] while BlaC was shown to posses signal sequence [26]. Few Lip gene family members (LipC, LipF), have been predicted as cytoplasmic, while later on these were confirmed as extracellular or membrane bound [27,28]. Therefore, the localization of Rv1497 needed to be explored further in detail.…”
Section: Discussionmentioning
confidence: 95%
“…A family of 24 carboxyl ester hydrolases called "lip" genes (lipC to Z, except K and S) has been predicted to play a role in lipid catabolism (14). Among these, only a few have been functionally characterized and related to mycobacterial dormancy and resuscitation (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Our earlier results with the recombinant proteins demonstrated that antibodies to PTRP and LipC were present in sera from 80–90% of the ∼50 of HIV+TB+ patients tested [7], [8]. While the number of HIV+TB+ patients whose sera have been included in the evaluation of reactivity with the BSA-peptide conjugates on the lateral flow format is small, and sera from larger cohorts will need to be examined, it is reassuring that the high sensitivity of anti-peptide antibody detection was obtained on the rapid format also.…”
Section: Discussionmentioning
confidence: 92%
“…Our earlier studies in the ELISA format had demonstrated that antibodies to these individual immunodominant epitopes are detected in sera from at least 40% of the TB patients tested, but not in subjects with latent M. tb infection [7], [8]. Moreover, since a vast majority of the specimens included were from India, where BCG vaccination is given at birth, antibodies to these peptides are also absent in the vaccinated individuals.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation